DEVELOPMENT OF INTEGRATED NATURAL SCIENCE MODULE BASED ON ETHNOSAINS THEMES OF ADDITIVE AND ADDICTIVE CLASS VIII SMP/MTs - Salni, Mufika (Universe, 2022)
This research is motivated by the low interest of students in science learning, and educators only use printed books and worksheets that are informative and also do not contain elements of local wisdom. Ethnoscience-based integrated science modules are able to increase students’ interest in learning and guide students to learn independently using these modules. The purpose of this study was to produce an integrated science module based on ethnoscience with the theme of additives and addictive substances for SMP / MTs. This research uses a Research and Development (R&D) developer research type using a 4-D model which consists of four stages, namely the Define, Design, Develop, and Disseminate stages. This study used a research instrument in the form of a questionnaire for the responses of educators and students to the developed module, namely the ethnoscience-based integrated science module. Based on the results of research that has been carried out, the modules that have been developed are included in the valid category with a value of 79.34%, the content competency variable gets a value of 79.25% with the valid category, the graphic variable gets a value of 82.38% very valid category, and language variables 76.67% included in the valid category.